Uma perspectiva histórica da construção da identidade da coordenadora pedagógica na rede municipal de Santo André, SP (1990-1998) - Fernandez, Michele (2024)
This study aimed to research the construction of the professional identity of the pedagogical coordinator in the municipal network of Santo André (SP), from a historical perspective, based on the appointment of the first positions created (1990-1998). The periodization framework covered the year of legal creation of the role of pedagogical coordinator in the municipal network of Santo André (1990), period of discussion of the democratization of education in the municipality, until the moment of incorporation of elementary education into the municipal network (1998). The research was carried out in the municipality of Santo André, an important city belonging to Greater São Paulo and was concerned with understanding how the role of pedagogical coordination was constituted over time, with regard to the initial and continued training of this professional, the creation of the position in the municipal network of Santo André, her relationship with the school management, how she articulated her training and pedagogical monitoring role and the challenges faced by the pioneer coordinators and how these aspects constitute important elements in the construction of the pedagogical coordinator's professional identity. The methodology used was qualitative, with the application of semi-structured interviews with retired pedagogical coordinators from the municipal network of Santo André and who worked during the period studied. The main theoretical framework of the research was Dubar (1997) and Nóvoa (1995). As a result, we understand that construction of the professional identity of the pedagogical coordinator of the municipal network of Santo André is a process that permeated and is still part of the profession today.There has always been a search to define the role of this professional in the network and how she actually develops it. As it was the beginning of the role on the network, everything was built during the execution of the activities. The continued training of this professional required a lot of investment in the first years of work.The formative role they played was well consolidated during theis period, but the pedagogical support for teachers did not occur effectively. The choice of these teachers, who could carry out coordination, always took place in accordance with the interests of the government that was in charge of the city’s management.These pedagogical coordinators who were part of the first generatión brought contributions and possibilites to the others who followed in the sequence.